2008
DOI: 10.1007/s10979-007-9100-1
|View full text |Cite
|
Sign up to set email alerts
|

The effects of accomplice witnesses and jailhouse informants on jury decision making.

Abstract: The present study presents one of the first investigations of the effects of accomplice witnesses and jailhouse informants on jury decision-making. Across two experiments, participants read a trial transcript that included either a secondary confession from an accomplice witness, a jailhouse informant, a member of the community or a no confession control. In half of the experimental trial transcripts, the participants were made aware that the cooperating witness providing the secondary confession was given an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
108
6
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(128 citation statements)
references
References 20 publications
12
108
6
2
Order By: Relevance
“…Over the years, mock jury studies have shown that confessions have a great impact on jury verdicts—a greater impact, for example, than eyewitness and character testimony (Kassin & Neumann, ). Research has also shown that people do not adequately discount confession evidence even when the confessions are perceived to have been coerced by police (Kassin & Sukel, ); even when jurors are told that the defendant suffers from a mental illness or interrogation‐induced stress (Henkel, ); even when the defendant is a juvenile (Redlich, Ghetti, & Quas, ; Redlich, Quas, & Ghetti, ); even when the confession was given not by the defendant but by a second‐hand informant who was motivated to lie (Neuschatz, Lawson, Swanner, Meissner, & Neuschatz, ; Neuschatz et al., ); and even, at times, when the confession is contradicted by exculpatory DNA (Appleby & Kassin, ).…”
Section: The Consequences Of Confessionmentioning
confidence: 99%
“…Over the years, mock jury studies have shown that confessions have a great impact on jury verdicts—a greater impact, for example, than eyewitness and character testimony (Kassin & Neumann, ). Research has also shown that people do not adequately discount confession evidence even when the confessions are perceived to have been coerced by police (Kassin & Sukel, ); even when jurors are told that the defendant suffers from a mental illness or interrogation‐induced stress (Henkel, ); even when the defendant is a juvenile (Redlich, Ghetti, & Quas, ; Redlich, Quas, & Ghetti, ); even when the confession was given not by the defendant but by a second‐hand informant who was motivated to lie (Neuschatz, Lawson, Swanner, Meissner, & Neuschatz, ; Neuschatz et al., ); and even, at times, when the confession is contradicted by exculpatory DNA (Appleby & Kassin, ).…”
Section: The Consequences Of Confessionmentioning
confidence: 99%
“…Once a confession is obtained, police tend to ''close'' cases as solved and refuse to investigate other sources of evidence, and prosecutors tend to charge suspects with the highest number and types of offenses, set bail higher, and are far less likely to initiate or accept plea bargains (Drizin & Leo, 2004;Leo & Ofshe, 1998; but see Redlich, in press). Mock jury studies have shown that confessions have more impact than other forms of evidence (Kassin & Neumann, 1997;Miller & Boster, 1977) and that people do not appropriately discount confession evidence-even when they judge the confession to be coerced and involuntary (Kassin & Wrightsman, 1980;Kassin & Sukel, 1997), when they say it does not influence their decisions (Kassin & Sukel, 1997), and when they are presented secondhand by an informant who is motivated to lie (Neutschatz, Lawson, Swanner, & Meissner, 2007). This literature suggests that, even when real world jurors recognize that interrogators used coercion to elicit confession evidence, this fact is not likely to temper their judgments of the defendant's guilt.…”
Section: Introductionmentioning
confidence: 99%
“…This effect has been discussed in jurors' attributions and evaluations of evidence in previous research. Jurors' assessments of jailhouse informants providing secondary confession information demonstrated the same pattern of attributions expected with the fundamental attribution error: participants indicated that their belief in the motivations causing the informant to come forward stemmed from internal, personal motives (e.g., his honesty or feelings of guilt) rather than from situation influences such as an incentive of money or reduced time on his sentence (Neuschatz, Lawson, Swanner, Meissner, & Neuschatz, ). Additionally, this effect seems to translate into guilty verdicts even when jurors can identify multiple potential reasons for why the informant might provide the information besides just dispositional factors (Maeder & Pica, ).…”
Section: Evidence Interdependence In Courtmentioning
confidence: 82%